GLP1R rs3765467 Polymorphism Is Associated with the Risk of Early Onset Type 2 Diabetes - Yunyun Fang; Jingjing Zhang; Linlin Ji; Chaoyu Zhu; Yuanyuan Xiao; Qingge Gao; Wenjing Song; Li Wei (International Journal of Endocrinology)
Objective. To investigate the relationship between glucagon-like peptide-1 receptor gene polymorphisms and susceptibility to early onset type 2 diabetes. Methods. Samples from 316 type 2 diabetes patients with early onset type 2 diabetes (n = 137) and late-onset type 2 diabetes (n = 179) and 145 nondiabetic individuals were analyzed. Multiplex PCR combined with resequencing Hi-Reseq technology was used to detect single nucleotide polymorphisms of the glucagon-like peptide-1 receptor gene, and the allele frequency, genotype distribution, and clinical parameters were analyzed between each diabetes subgroup and the control group. Results. Sixteen single nucleotide polymorphisms were identified in the exonic region of the glucagon-like peptide-1 receptor gene according to the minor allele frequency (MAF > 0.05) in the participants. Among these, the glucagon-like peptide-1 receptor rs3765467 (G⟶A) mutation was statistically associated with early onset type 2 diabetes. Compared with that of the GG carriers, carriers of genotype AA at rs3765467 had a decreased risk of early onset type 2 diabetes after adjusting for sex and body mass index. In the dominant model, the frequencies of the rs3765467 AA + GA genotype were significantly decreased in the early onset type 2 diabetes group, and carriers of genotype AA + GA at rs3765467 had a decreased risk of early onset type 2 diabetes after adjusting for sex and body mass index. Moreover, fasting C peptide levels were significantly higher in GA + AA genotype carriers than those in GG genotype carriers. Conclusion. The glucagon-like peptide 1 receptor rs3765467 polymorphism was significantly associated with age at type 2 diabetes diagnosis and thus may be used as a marker to screen and detect individuals at risk of developing early onset type 2 diabetes.